Unveiling the pharmacological potential of Murraya koenigii against diabetic nephropathy - Randhir Singh; Shah Asma Farooq Sushma Devi
This study aimed to explore the efficacy of various extracts derived from Murraya koenigii (L.) in managing diabetic nephropathy (DN). DN was induced via intraperitoneal administration of streptozotocin (65 mg/kg), following a 15-minute pre-treatment with NAD (230 mg/kg), to develop diabetes. Evaluation of DN involved monitoring level of fasting blood glucose, glycated haemoglobin, serum insulin, albuminuria, serum urea, uric acid, creatinine, BUN, and alterations in lipid profile (TC, TG, LDL, and HDL). The oral administration of hydroalcoholic extract derived from Murraya koenigii to diabetic rats showed a notable improvement in renal dysfunction, as demonstrated by a marked decrease in inflammatory markers. Moreover, the treated groups experienced significant increase in body weight and notable reductions in fasting blood glucose and glycated haemoglobin levels. The administration of the extracts also effectively alleviated hyperglycemia-induced oxidative stress, evidenced by a noteworthy rise in superoxide dismutase (SOD) and reduced glutathione (GSH) levels, coupled with a considerable decrease in malondialdehyde (TBARS) levels. Additionally, the treatment led to the reversal of histopathological abnormalities observed in the kidneys, pancreas, and liver of diabetic rats.These findings indicate that treatment with M. koenigii extracts alleviated DN.